Encyclopedia of Environmetrics 2001
DOI: 10.1002/9780470057339.vac061
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Scale Morphology

Abstract: The scaling of physical, biological, ecological and social phenomena has become a major focus of efforts to develop simple representations of complex systems. Much of the attention has been on discovering universal scaling laws that emerge from simple physical and geometric processes. But there are regular patterns of departures both from those scaling laws and from continuous distributions of attributes of systems; these departures often demonstrate the development of self‐organized interactions between livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…These include invasion, extinction, high population variability, migration, and nomadism (Allen et al 1999, Allen and Holling 2002, Wardwell and Allen 2009. Additionally, the roles that species play and the distribution of the functional attributes of these species within and across scales may strengthen the resilience of ecological systems (Peterson et al 1998, Walker et al 1999.…”
Section: Extensions To Original Frameworkmentioning
confidence: 99%
“…These include invasion, extinction, high population variability, migration, and nomadism (Allen et al 1999, Allen and Holling 2002, Wardwell and Allen 2009. Additionally, the roles that species play and the distribution of the functional attributes of these species within and across scales may strengthen the resilience of ecological systems (Peterson et al 1998, Walker et al 1999.…”
Section: Extensions To Original Frameworkmentioning
confidence: 99%
“…A critical issue to be resolved before confronting alternate hypotheses with data is determining how to rigorously quantify patterns in body mass distributions, and compare different distributions. Few rigorous methods exist for the detection of such pattern (Allen & Holling 2001). For example, how much of a shift is necessary to say a mode or gap in a distribution is in a new location when comparing body mass distributions?…”
Section: Sifting Among the Alternative Hypothesesmentioning
confidence: 99%
“…A number of methods have been suggested, including null models and simulations (Manly 1996;Restrepo and others 1997), cluster analysis and split moving window boundary analysis, and difference indices (Allen and Holling 2001). Because each method has its own shortcomings and advantages, Allen and Holling (2001) concluded that the best approach is to use multiple methods and compare the resulting structures, searching for agreement among as many methods as possible. Identification of discontinuities determines the location and number of aggregations within a system.…”
Section: The Use Of Discontinuities To Assess Relative Resiliencementioning
confidence: 99%